Efficacy analysis of comprehensive rehabilitation therapy based on the Gesell developmental schedules among infants with global developmental delay of different ages: a retrospective study - Dan Liu; Mo Duan; Cuiying Chen; Jianhua Xue; Ling Yue (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to analyze differences in efficacy using the Gesell Developmental Schedules (GDS) among infant patients with global developmental delay (GDD), thereby providing an objective basis for early intervention.MethodsA retrospective analysis was performed of 155 infants with GDD who were first diagnosed and admitted to the neurorehabilitation department of our hospital between January 2022 and December 2024. The data collected included general information, maternal pregnancy and perinatal data, and GDS results of the patients. The patients were divided according to their age into 3–6, 7–12, and 13–18-month groups. All patients received at least 3 months of comprehensive rehabilitation therapy, and the GDS was used to assess pre- and post-treatment efficacy.ResultsAccording to the logistic regression analysis, age at initial diagnosis, prematurity, and neonatal asphyxia were identified as risk factors for poor prognosis (OR > 1, p < 0.05). The pre- and post-treatment difference in the total developmental quotient (DQ) of the five domains (adaptive, gross motor, fine motor, language, and personal-social) were significantly higher in the 3–6-month group than in the 7–12- and 13–18-month groups (p < 0.05) and did not differ significantly from the pre-post difference in total DQ between the 7–12- and 13–18-month groups (p > 0.05). The 3–6-month group had significantly higher pre-post DQ differences in the five domains than the 7–12- and 13–18-month groups (p < 0.05). The 7–12- and 13–18-month groups did not differ significantly with respect to pre-post DQ differences in any of the five domains (p > 0.05). Regarding the levels of the GDS adaptive domain, the number of cases at each level differed significantly before and after treatment in the 3–6-month group (p < 0.05).ConclusionComprehensive rehabilitation interventions showed significant efficacy in infants aged 3–6 months.